Impact of Adherence to the Mediterranean Diet on Antioxidant Status and Metabolic Parameters in NAFLD Patients: A 24-Month Lifestyle Intervention Study - Maria Magdalena Quetglas-Llabrés; Margalida Monserrat-Mesquida; Cristina Bouzas; Silvia García; Emma Argelich; Miguel Casares; Lucía Ugarriza; Isabel Llompart; Josep A. Tur; Antoni Sureda (MDPI AG, 2024)
Background: The Mediterranean Diet (MedDiet) is recognized as a healthy dietary pattern. Non-alcoholic fatty liver disease (NAFLD) is characterized by the excessive accumulation of fat in the liver. Objectives: To assess the antioxidant status in erythrocytes, plasma, and peripheral blood mononuclear cells (PBMCs) of NAFLD patients following a 24-month lifestyle intervention based on the MedDiet. Adult patients (n = 40; aged 40-60 years) diagnosed with NAFLD by magnetic resonance imaging were divided into two groups based on their adherence to the MedDiet. Consumption was assessed using a validated 143-item semiquantitative Food Frequency Questionnaire. Anthropometrics, biochemistry parameters, intrahepatic fat contents (IFC), antioxidants, and inflammatory biomarkers were measured in plasma and erythrocytes before and after the intervention. Results: After the intervention, body mass index (BMI) and plasma levels of total cholesterol, low-density lipoprotein cholesterol (LDL-chol), triglycerides, malondialdehyde (MDA), and cytokeratin-18 (CK18) decreased, and high-density lipoprotein cholesterol (HDL-chol) increased. Participants with high adherence to MedDiet showed lower IFC, hepatic enzyme (AST, ALT, and GGT), glycemia, oxidase LDL (oxLDL) plasma levels, and erythrocyte MDA levels. Higher antioxidant activity (erythrocyte catalase-CAT, superoxide dismutase-SOD, glutathione peroxidase-GPx, glutathione reductase-GRd, and total glutathione-GSH as well as PBMCs-CAT gene expression) was observed in these patients, along with a reduction of PBMCs reactive oxygen species production and Toll-like receptor 4 (TLR4) expression. Inverse associations were observed between adherence to the MedDiet and BMI, glycemia, AST, IFC, and CK18 plasma levels and oxLDL, CAT, SOD, and GRd activities in erythrocytes. A significant linear regression was observed between adherence to the MedDiet and antioxidant score. Conclusions: Adherence to the MedDiet is associated with improved plasma and PBMC antioxidant and inflammatory biomarker profiles and high antioxidant defences in erythrocytes.